Potassium ion in physiology and cardiovascular disorders - Knypl, Krystyna (Przewodnik Lekarza/Guide for GPs, 2006)
Potassium is one of the most important ions in the body. Potassium has many physiological functions, including cellular metabolism, glycogen and protein synthesis and regulation of the electrical action potential across cell membranes, especially in the myocardium. Approximately 98% of total body potassium is found in the intracellular space, with approximately 2% in the extracellular space. The normal serum potassium concentration is 3.5-5.0 mEq/l. Hypokalemia is defined as a serum potassium concentration below 3.5 mEq/l. Hypokalemia signs and symptoms involve changes in muscle and cardiovascular functions, but it can also manifest itself as weakness, nausea or vomiting.